MO1046DOPING POLYSULFONE DIALYSIS MEMBRANES WITH HUMAN NEUTROPHIL ELASTASE INHIBITORS - A PILOT STUDY. (29th May 2021) - Rocha, Susana; Morgošová, Kristína; Valente, Maria João; Amorim, Célia; Araújo, Alberto; Santos-Silva, Alice; Moreira, Rui; Branco da Silva Montenegro, Maria Conceição
Abstract: Background and Aims: During hemodialysis (HD) therapy, the long-term intradialytic contact of blood with large surfaced artificial materials (HD membranes) leads to continuous neutrophil activation, with the release of neutrophil elastase (NE), among other products. NE appears to contribute to enhance inflammation favoring the development of atherosclerosis, which is the main cause of mortality and morbidity in End-Stage Renal Disease patients. The modification of polysulfone (PSF) HD membranes by incorporating selective human NE inhibitors (NEIs) might reduce the inflammatory response and prevent HD associated complications. Thus, the present study aimed to dope PSF membranes with NEIs and assess their bioactivity and biocompatibility. Method: As NEIs, it was used the commercially available Sivelestat (SIV), from Abcam, and an in house synthetized 4-oxo-β-lactam (D4L-3) based compound, selected from our library, and prepared as described elsewhere [1]. The PSF membranes were prepared according to [2] and further doped with each NEI by adsorption. Three independent assays were performed (in triplicates) where PSF membrane circles (2 cm in diameter) were incubated with ultrapure water (blank), NEIs vehicle (2.5% DMSO) or with 10 - 2000 nM SIV or D4L-3. The bioactivity of these modified PSF membranes was evaluated by a human NE activity assay [1]. The same method was used to determine the IC50 of both NEIs in solution. Biocompatibility assays ( n = 3) were carried-out using duplicates of modified PSF membranes circles with Ø 2 cm incubated with 1.0 mL of whole-blood. After incubation, platelet (PLT) poor and PLT rich plasma were used to assess the levels of plasma hemoglobin (Hb) and PLT activation, respectively [2]. Results: The IC50 of SIV and D4L-3 in solution were 30.9 and 87.6 nM, respectively. For PSF membranes doped with NEIs, their bioactivity increased in a concentration-dependent manner, with the highest NE inhibition of 44 and 22 % at 2000 nM SIV and D4L-3, respectively. The blank membranes showed the highest hemolytic capacity, whereas SIV and D4L-3 PSF membranes presented lower plasma Hb levels when compared with the blank or the vehicle; on average, SIV-PSF membranes presented 31% less plasma Hb than vehicle, while in D4L-3-PSF this decrease was of 51%. Regarding the thrombotic potential of these biomaterials, blank membranes presented slightly increased PLT activation levels when compared to vehicle, and modified SIV-PSF membranes showed, on average, 58% more PLT activation than the vehicle, while D4L-3-PSF membranes displayed 25% less, on average. Conclusion: The successful adsorption of NEIs into PSF membranes was achieved and the NE inhibition ability was directly dependent on the concentration of the inhibitor utilized. Moreover, the bioactivity of SIV and D4L-3 when immobilized into PSF membranes it appears to follow their inhibitory capacity occurring in solution, with SIV showing a greater affinity for NE. However, concerning biocompatibility, D4L-3 displayed a greater safety performance than SIV, especially regarding the potential for triggering platelet activation. To ensure the applicability of these modified PSF membranes as a medical device, extensive further studies have to be carried-out by tweaking the conditions of the immobilization process in order to obtain an optimal equilibrium between bioactivity and biocompatibility, as well test new NEIs. Acknowledgments: This work was supported by UIDB/50006/2020 and UIDB/04378/2020 with funding from FCT/MCTES through national funds, and by the project Dial4Life co-financed by FCT/MCTES (PTDC/MEC-CAR/31322/2017) and FEDER/COMPETE 2020 (POCI-01-0145-FEDER-031322).